In Vivo Tumorigenesis Was Observed after Injection of In Vitro Expanded Neural Crest Stem Cells Isolated from Adult Bone Marrow - Wislet-Gendebien, Sabine; Poulet, Christophe; Neirinckx, Virginie; Hennuy, Benoit; Swingland, James T.; Laudet, Emerence; Sommer, Lukas; Shakova, Olga; Bours, Vincent; Rogister, Bernard (PLOS ONE, 2012)
Bone marrow stromal cells are adult multipotent cells that represent an attractive tool in cellular therapy strategies. Several studies have reported that in vitro passaging of mesenchymal stem cells alters the functional and biological properties of those cells, leading to the accumulation of genetic aberrations. Recent studies described bone marrow stromal cells (BMSC) as mixed populations of cells including mesenchymal (MSC) and neural crest stem cells (NCSC). Here, we report the transformation of NCSC into tumorigenic cells, after in vitro long-term passaging. Indeed, the characterization of 6 neural crest-derived clones revealed the presence of one tumorigenic clone. Transcriptomic analyses of this clone highlighted, among others, numerous cell cycle checkpoint modifications and chromosome 11q down-regulation (suggesting a deletion of chromosome 11q) compared with the other clones. Moreover, unsupervised analysis such as a dendrogram generated after agglomerative hierarchical clustering comparing several transcriptomic data showed important similarities between the tumorigenic neural crest-derived clone and mammary tumor cell lines. Altogether, it appeared that NCSC isolated from adult bone marrow represents a potential danger for cellular therapy, and consequently, we recommend that phenotypic, functional and genetic assays should be performed on bone marrow mesenchymal and neural crest stem cells before in vivo use, to demonstrate whether their biological properties, after ex vivo expansion, remain suitable for clinical application.